Water Quality Analysis in the Batang Ombilin River, Sawahlunto City - Fitrya Monica; Iswandi Umar; Indang Dewata; Eri Barlian (Jurnal Penelitian Pendidikan IPA, 2023)
The decline in water quality is caused by pollution pressure due to low environmental sanitation efforts. Water quality can be determined by carrying out certain tests on the water. This research was conducted on the Batang Ombilin River, Sawahlunto City. This research was conducted in October 2022. This research used survey methods and laboratory test methods. Activities carried out using the survey method are in the form of interviews related to research. Next, laboratory test methods are used to analyze water quality. Interview activities were carried out with people living around the Batang Ombilin River. Respondents were determined using random sampling. Samples were taken of 2 liters of water and carried using plastic bottles. The parameters used to see water quality are TDS, TSS, pH, DO, BOD and COD. Based on research that has been carried out, the results show that 65.25% of respondents stated that the existing water is suitable for consumption but must be filtered and purified first before cooking. Meanwhile, 30.75% of respondents stated that it was not suitable for consumption because the water was cloudy, dirty and smelly. Furthermore, in the water quality analysis, the average value of the TDS parameter was obtained with an average value of 108. TSS obtained an average value of 29.1. The pH got an average value of 8.1. DO got an average score of 7.3. BOD got an average score of 1.4 and COD got an average score of 15.2. From the results of tests carried out at 3 different points, an average value was obtained below the established class 2 water quality standards